Unsettling transcription through “event memory”: problem and possibility in exploring the phenomenological question - Sinclair, Meredith N. (Qualitative Inquiry, 2020)
This article works to unsettle the use of transcription in qualitative inquiry by troubling the truth claims of transcribed text. Building on the hermeneutic phenomenology of Van Manen, it explores the way the researcher might “write through” transcribed text to return to the two-dimensional text space a more honest reading of lived experience. It also draws on Deleuze and Guattari’s rhizomatic thinking to explore the “gruesome multiplicities” present in reality—and the ways we might honor that multiplicity in research texts. Excerpts from an inquiry into the phenomenon of “reading as not a reader” are used to illustrate.
1 citations (Crossref) [2023-10-31] tex.ids: lens.org/070-679-779-525-700, pop00318, sinclairUnsettlingTranscriptionEvent2018, sinclairUnsettlingTranscriptionEvent2018a, sinclairUnsettlingTranscriptionEvent2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85059284090 tex.type: [object Object] type: Article
Keywords: dept.eng; hermeneutic phenomenology; methodologies; methods of inquiry; peer-reviewed; qualitative research; qualitative research and education; transcription; writing as method of inquiry